Genetic Diversity in Invasive Populations of Lupinus polyphyllus Lindl. and Heracleum sosnowskyi Manden. - Ekaterina Sergeevna Osipova (MDPI AG, 2021)
In our study, two aggressive-invasive species, Lupinus polyphyllus Lindl. and Heracleum sosnowskyi Manden. from Russia and Ukraine, were investigated. The success in naturalization of both species is associated with human activities, since they have been used in agriculture and floriculture and both have qualities such as environmental tolerance, high fertility and phenotypic plasticity. The purpose of this study was to determine the level of genetic diversity of both species. For Heracleum sosnowskyi Manden., genetic diversity was compared in invasive and native populations. For Lupinus polyphyllus Lindl., the genetic diversity was compared in variety, feral and invasive populations. A genetic diversity was formulated using RAPD, ISSR and REMAP. For Heracleum sosnowskyi Manden., the average genetic diversity within the invasive population was similar (0.432), but slightly less (0.502) than within the native Caucasian population. This may suggest the successful naturalization of invaders and almost complete reconstruction of their genetic diversity. For Lupinus polyphyllus Lindl., the genetic diversity for the invasive population was the highest, with an average of 0.294, while for variety, it was the lowest, with an average of 0.194. The feral population had an intermediate place with an average of 0.248, which could suggest an increase of diversity in the process of naturalization.